Dynamic control and performance of dual active bridge converter based particle swarm optimization - Suliana, Ab Ghani; Hamdan, Daniyal; Norazila, Jaalam; Norhafidzah, Mohd Saad; Nur Huda, Ramlan (Institution of Engineering and Technology, 2022)
This paper presents analysis of the dynamic response of the isolated bidirectional dual active bridge (DAB) DC-DC converter using particle swarm optimization (PSO) algorithm. On the basis, the fast dynamic response is one of the main control objective for DAB system to ensure the system able to have fast time recovery and adapt with various control environment. A 200 kW DAB system with single-phase shift (SPS) modulation is tested for direct and indirect online tuning phase-shift angle, ϕ using PSO algorithm. In direct tuning, the optimal ϕ is directly tuning using PSO. While in indirect tuning method, the optimal values of PI parameters are functioning to well-tuned the desired ϕ in the DAB system, where both values of KP and KI have been optimized using the PSO algorithm. The DAB performance with both proposed methods is evaluated in terms of dynamic response for load step changes under various reference voltages. Comparative analysis between direct and indirect methods are carried out using hardware in-the-loop (HIL) experimental. The DAB with indirect online tuning produces 11.50ms faster response compared to the direct online tuning method.